Pendidikan dan Latihan: Merancang Kegiatan Menyenangkan untuk Mengembangkan Kemampuan Berpikir Simbolik Bagi Anak Usia Dini - Vanida Mundiarti; Sartika Kale; Irul Khotijah; Engelbertus Nggalu Bali (Universitas Nusa Cendana, 2023)
The training activities carried out are solutions to the problems found, especially in designing activities that can stimulate symbolic thinking skills for early childhood. The training activities were carried out in two sessions, the first session was the provision of material by resource persons and the second session was the practice of compiling activities to stimulate children's symbolic thinking skills. The final results of the activity show that there is an additional teacher's understanding of children's symbolic thinking abilities, and the teacher's skills in designing fun activities to provide stimulation in an effort to improve children's symbolic thinking skills.